1977
DOI: 10.1021/ac50022a019
|View full text |Cite
|
Sign up to set email alerts
|

Supply and removal of sample vapor in graphite thermal atomizers

Abstract: 3. In the absence of interferents, the precision and detection limits of SWS and DWS are normally comparable. DWS may, however, be more precise than SWS where the latter measurement has substantial associated sample presentation error.In the presence of interferents, DWS precision is markedly reduced because of increase of independent and square root errors. In particular, dark current noise may become significant under these conditions. 5. The use of very small wavelength differences, as in differential spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0
3

Year Published

1986
1986
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 192 publications
(54 citation statements)
references
References 31 publications
6
45
0
3
Order By: Relevance
“…Also, before comparison can be made, it must be noted that the efficiency values determined in this study were for the HGA-400, and were only applicable under the specific experimental conditions, especially the heating rates used in this work. The most important difference between this work and those of the above authors was that the heating rates used in this work were much higher (Table 2) than those used by the above authors (1,2). Regardless of whether atomization was isothermal or nonisothermal, higher heating rates increased k I values much more than k 2 values, and hence decreased t,;,, values by eq.…”
Section: Comparison With the Atornization Eflciency Values Reported Bymentioning
confidence: 61%
See 4 more Smart Citations
“…Also, before comparison can be made, it must be noted that the efficiency values determined in this study were for the HGA-400, and were only applicable under the specific experimental conditions, especially the heating rates used in this work. The most important difference between this work and those of the above authors was that the heating rates used in this work were much higher (Table 2) than those used by the above authors (1,2). Regardless of whether atomization was isothermal or nonisothermal, higher heating rates increased k I values much more than k 2 values, and hence decreased t,;,, values by eq.…”
Section: Comparison With the Atornization Eflciency Values Reported Bymentioning
confidence: 61%
“…Table 4 shows that most of the atomization efficiencies reported by Sturgeon and Berman (1) are of the same order of magnitude as those of this work. van den Broek and de Galan (2) reported that atomization efficiency of the HGA-72 for Ag -a theoretical value of 0.45 and experimental value of 0.20. These authors (2) defined the atomization efficiency as N,,,/No -the ratio of the maximum number of atoms, N,,, (obtained from the measured peak absorbance), and the amount of analyte injected into the furnace, No.…”
Section: Comparison With the Atornization Eflciency Values Reported Bymentioning
confidence: 98%
See 3 more Smart Citations